Report on an Unannounced Inspection of Magilligan Prison 12-22 June 2017. (2017) - Northern Ireland., Criminal Justice Inspectorate,; Great Britain., Her Majesty's Chief Inspector of Prisons for England; Wales,; Northern Ireland., Department of Education., Education; Training Inspectorate,; Northern Ireland., Regulation; Quality Improvement Authority,
No abstract available